Fístula bronquioesofágica asociada a reflujo gastroesofágico - Padilla Flores, Juan Roberto (2019)
We present a clinical case of bronchoesophageal fistula associated with gastroesophageal reflux in a 76-year oldman with a diagnosis of gastroesophageal reflux and hernia. He comes for episodes of cough of 1 year of evolution without response to treatments. We will demonstrate the usefulness of the esophagographic study as a diagnostic element. The clinical, diagnostic, therapeutic aspects and the probably sequence of development of this complication are briefly reviewed.